Process Philosophy and Exceptional Experience: Whitehead and the Wild(er)ness of Non-Sensory Perception. - Davis, Andrew M. (Zygon: Journal of Religion & Science, 2026)
The purpose of this article is to demonstrate and elucidate the fruitfulness of Alfred North Whitehead's doctrine of non-sensory perception for exceptional forms of experience. I begin by introducing Whitehead's work, influence, and some of the characteristic ideological transitions associated with his thought. I then draw attention to his methodology as a form of radical empiricism beyond that of William James and review some of his central critiques of philosophy and science in light of them. Against the problematic modern assumption that all experience is mediated through the clarity of conscious sense perception, I then move to articulate his wilder doctrine of the primacy of non-sensory perception, of which conscious sense perception is a heightened, albeit narrower, delimitation, showing that this dual theory of perception provides a viable conceptual means of approaching exceptional forms of experience. Turning to recent examples of process philosophers extending and applying Whitehead's doctrine of perception, I focus on religious or mystical experiences of God, paranormal or parapsychological phenomena, and psychedelic experiences. Finally, I connect the discussion to recent neuroscience, suggesting that the hemisphere hypothesis of Iain McGilchrist may provide neuroscientific support for Whitehead's dual theory of perception, including the conviction that the function of the brain with respect to the mind is not to produce the mind as such but to limit its inclusion so that waking consciousness is actually possible. I conclude by briefly commenting on the nature and importance of spiritual practice.